Agricultural value chain finance with four actors: Advantages and disadvantages - de Brauw, Alan (International Food Policy Research Institute, 2024)
Smallholder farmers in low- and middle-income countries (LMICs) face multiple constraints that often constrain them against participating in the production of high value products. Even where it is agroeco logically possible or even advantageous to produce specific products, smallholders may lack knowledge about how to grow those products and may also lack market information for those products. As smallholders typically lack access to formal financial institutions, their ability to borrow, save, or in sure against risks associated with growing those products is limited. These challenges combine to make it difficult for smallholders to participate in markets that could increase their incomes.